An Overview of Traffic Accident Investigation Using Different Techniques - Shireen Ibrahim Mohammed (Automotive Experiences, 2023)
One of the most important aims of incident management is the clearance of the incident scene as fast as possible. The accident Investigation provides physical evidence at the accident site for the investigators. This physical evidence is much more reliable than the witness's statements and they are very crucial for the incident reconstruction. The cars accidents investigation is a dangerous activity, so it should be undertaken with suitable, accurate, and fast equipment. Many law enforcement agencies in the world have used different surveying techniques for accident investigations including the coordinate method, total station, photogrammetry, laser scanner, etc. Therefore, this research has been carried out in order to introduce the benefits of using surveying techniques in traffic accident investigations, and show their impacts on evidence documentation and scene clearance. This is done by focusing on the advantages and the disadvantages of each method based on the relevant works of literature and compares between them. Although comparison result shows that the traditional method(coordinate method) is simpler and cheaper than other methods, surveying techniques methods are safer, and faster in clearing the accident scene, fewer investigators are needed, the scale can be provided directly, high accuracy measurements can be obtained, and three dimensions models can be produced. So it's worth using the surveying equipment in cars accidents investigations.